USING GOOGLE CLASSROOM AS AN EFFECTIVE WAY TO COLLECT STUDENTS’ ASSIGNMENTS - Marsika Sepyanda (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2024)
Nowadays, information and technology develop through society development and need. The development brings positive impact for education, especially in teaching and learning process. One of the impacts is blended learning that has been created to make teaching and learning process run better than before. Blended learning means to combine conventional and online class. One of IT products related to blended learning is Google Classroom, an application that has been developed by Google Inc. Using Google Classroom in teaching and learning process can help the lecturer to collect students’ assignment effectively, because collecting students’ assignment usually take much more time while the activity is limited by the time allocation.